FACTORS INFLUENCING HEALTHCARE SEEKING BEHAVIOUR AT PRIMARY HEALTHCARE LEVEL, IN PAKISTAN - Hussain, Rizwana; Rashidian, Arash; Hafeez, Assad; Mirzaee, Negar (Journal of Ayub Medical College Abbottabad, 2019)
Background: The objective of this study is to explore the factors which influence the health seeking behaviour and utilization of healthcare services of the community in context of geographical, socio-demographic, cultural, economic and educational background. Methods: A community based cross-sectional survey was performed on 900 households in five districts of Punjab from 1st February to 2nd March, 2016. In each of the selected district random sampling method was used for selection of six primary health facilities. 900 household purposively selected around each selected PHCF in opposite direction at distance of 5, 10, 15 km. A pretested questionnaire, WHO operational package (for assessing, monitoring and evaluating country pharmaceutical situations Level IIb) was acquired, and analysed by SPSS 23. Results: In 900 households visited, total population was 5024, out of which females and males were 47.7% and 52.3%respectively. About 95% of community had source of income. The male respondents and females were 95% and 5% respectively. 43.3% of patients visited PHCF, were with the serious complaints. 37% patients in households didn't take medicines when got sick. Females who completed their primary education were same in number as male but after primary education, males were more who perused further education. For 14% of the respondents, PHC was too far and for 61.9% of the respondents, PHC was close to reach.74.5% of the respondents were not satisfied with timings. 42.7% got medicines they need from PHC. Community with access <15 min to PHCF were 57.2%, and >1 hour was 5%. 49.1% of respondents could get free medicines from PHC. 64.4% respondent found medicines expensive at private pharmacies. In 53.3% of the cases, prescriber was doctor and for 47.6% were trained health assistant. Conclusion: There is a potential to improve the health seeking behaviour and PHC utilization by addressing the demand-side (community) factors created by geographical access, socio-economic factors, level of education, cultural beliefs and by healthcare system itself. Male dominance was found. Level of education was more among males. Physical access was a significant barrier. Availability of medicines was low. There was absence of doctor at PHCF. Keywords: Health seeking behaviour; primary healthcare; barriers